2008
DOI: 10.1007/s00431-008-0698-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after renal transplantation in children from native and immigrant families in Austria

Abstract: Renal transplantation is the therapy of choice for children with end-stage renal disease (ESRD). Ethnicity affects the transplant survival rates substantially, but there has been no European academic evaluation of the effects of immigration on the pediatric renal transplantation outcome. The aim of this study was to compare the outcomes of renal transplantation between the children of immigrant families and the children of native families at the pediatric nephrology unit of the Medical University of Vienna, Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
5
10
0
Order By: Relevance
“…In the immigrant as well as in the native cohort, outcomes improved significantly during the decades, as expected. These data confirm the results of our pilot study in 57 RTx children in 2005 that also found no influence of migration status on patient or graft outcomes [12]. Moreover, the consistency of a similar outcome over the total observation period of more than 30 years adds to the validity these findings.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the immigrant as well as in the native cohort, outcomes improved significantly during the decades, as expected. These data confirm the results of our pilot study in 57 RTx children in 2005 that also found no influence of migration status on patient or graft outcomes [12]. Moreover, the consistency of a similar outcome over the total observation period of more than 30 years adds to the validity these findings.…”
Section: Discussionsupporting
confidence: 92%
“…The rate of acute rejection episodes decreased from 87.5% during the first decade to 32.8% during the last decade (p<0.01), and the e-GFR 1 increased from 55.3±14.8 to 64.4±27.8 (p=0.01) and e-GFR 2 improved from 42.3± 15.8 to 52.2±19.2 (p=0.06). All of these outcome parameters improved in parallel form in native and immigrant children, and remained comparable, which is in accordance to our results reported earlier [12].…”
Section: Transplantation Datasupporting
confidence: 95%
See 3 more Smart Citations